Recent Patents on Cu/low-k Dielectrics Interconnects in Integrated Circuits - Jiang, Qing; Zhu, Yong F.; Zhao, Ming (Recent Patents on Nanotechnology, 2007)
In past decades, the development of microelectronics has moved along with constant speed of scaling to maximize transistor density as driven by the need for electrical and functional performance. For further development, the propagation velocity of electromagnetic waves becomes increasingly important due to their unyielding constraints on interconnect delay. To minimize it, it was forced to the introduction of the Cu/low-k dielectric interconnects to very large scale integrated circuits (VLSI) where k denotes the dielectric constant. In addition, reliable barrier structures, which are the thinnest part among the device parts to maximize space availability for the actual Cu IWs, are required to prevent penetration of different materials. In light of the above statements, this review will focus recent patents and some studies on Cu interconnects including Cu interconnect wires, low-k dielectrics and related barrier materials as well manufacturing techniques in VLSI, which are one of the most essential concerns in microelectronic industry and decides the further development of VLSI. In addition, possible future development in this field is considered.
Keywords: very large scale integrated circuits